A epidemiological characteristics of SARS-Cov-2 and aspects of dental management - Paltas Miranda, Mayra (2020)
Despite the measures implemented worldwide, the spread of the new SARS-CoV-2 coronavirus is on the rise, which is why it is important to know the characteristics of the disease, as well as different considerations to take into account in dental clinical management. This pandemic obliges all health professionals to know their epidemiological characteristics, in order to generate preventive measures and care protocols that are necessary and important in these cases, respecting the biosafety regulations in order to avoid contagions between patient-professionals and professionals-patients. In the dental area, most clinical procedures are related to the direct contact of aerosols,  which are a considerable source of contamination, which is why in this work a review of the epidemiological aspects of COVID-19 and the care to be taken in dental care.